Penggunaan Media Cerita Bergambar dalam Meningkatkan Kemampuan Bahasa Ekspresif Anak Usia Dini - Salma Nur Fauziah; Syifa Nurul Fu'adah; Meisha Tri Hapsari; Budi Iskandar (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
Expressive language skills in early childhood are a crucial aspect of communication development that need to be stimulated through approriate learning. The purpose of this study is to describe the use of picture storybooks in improving expressive languange skills in children aged 5-6 years. This study employed a descriptive quantitative approach with 30 early childhood education teachers in Tasikmalaya as the research subjects. Data were collected using a Likert scale questionnare based on languange development indicators in the STTPA. The result showed that the use of picture storybook obtained and overall mean score of 4.21 (84.3%) categorized as very good. This media proved effective in increasing children’s learning interest, active speaking, ability to answer questions, courage to ask questions, and ability to retell story contect. Picture storybooks are recommended as an effective instructional media alternativen to stimulate expressive languange developmentt in early chillhood